MENGINTEGRASIKAN PSIKOLOGI: PELUANG ATAU MIMPI? - T. Dicky Hastjarjo (Faculty of Psychology Universitas Gadjah Mada, 2008)
“How can institutional psychology be taken seriously when psychologists themselves disagree over fundamental issues such as how to define or investigate the discipline’s core subject matter” (Yanchar, 2000, h. 248).